2015
DOI: 10.1002/jbm.a.35431
|View full text |Cite
|
Sign up to set email alerts
|

The significance of grafting collagen on polycaprolactone composite scaffolds: Processing–structure–functional property relationship

Abstract: The study concerns processing-structure-functional property relationship in organic-inorganic hybrid scaffolds based on grafted collagen for bone tissue engineering. Biodegradable polyester, polycaprolactone (PCL) and nanohydroxyapatite were used to fabricate three-dimensional porous scaffolds by adopting a combination of solvent casting, particulate leaching, and polymer leaching approaches. The PCL scaffold was subsequently surface modified by chemical bonding of 1,6-hexanediamine to the ester groups of PCL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…In this study, a biodegradable synthetic polymer, polycaprolactone (PCL), and a natural polymer, gelatine (Ge), were used. Both of these polymers have been approved by the Food and Drug Administration (FDA) and are safe for use in the human body (Kiran et al 2014 ; GMIA 2012 ). Some studies have observed that PCL fibrous scaffolds cause a reduction in cell attachment, migration, proliferation, and differentiation (Jin et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a biodegradable synthetic polymer, polycaprolactone (PCL), and a natural polymer, gelatine (Ge), were used. Both of these polymers have been approved by the Food and Drug Administration (FDA) and are safe for use in the human body (Kiran et al 2014 ; GMIA 2012 ). Some studies have observed that PCL fibrous scaffolds cause a reduction in cell attachment, migration, proliferation, and differentiation (Jin et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…A key component in determining the viability of the scaffold is to observe the behaviour of the fibroblastic cells on the membranes. Collagen is a major constituent of the ECM, bearing the motifs to which cell integrins bind [45], and as such, scaffolds conjugated with collagen displayed a much higher level of cellular growth and adhesion [20,21,46]. A Live/Dead assay (Figure 8) on the same sample area showed a greater quantity of live cells on PHBV-Collagen than the PHBV surface.…”
Section: Discussionmentioning
confidence: 99%
“…As a means to tailor the biological or mechanical function of PHBV scaffolds, blends, and composites with other natural or synthetic biopolymers [10][11][12][13][14], and bioceramics [15][16][17][18] have been studied. In particular, collagen type-I, which is the most abundant protein in the ECM [19] and responsible for the integrity of the tissue, is one of the most commonly investigated materials for TE scaffolds and as a coating or component in composite TE scaffolds [20][21][22]. Collagen type-I possesses structural motifs to which cell integrins bind [23], mediating cellular adhesion and migration in the native ECM [24].…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the development of 3D additive manufacturing methods, the methods adopted to fabricate 3D porous scaffolds include freeze drying, solvent casting with particulate leaching, fiber bonding, membrane lamination, and gas foaming [16,[57][58][59]. In these methods, it is difficult to control the pore size, shape, and pore interconnectivity [60].…”
Section: D Additive Manufacturing Methods For Bone Tissue Engineeringmentioning
confidence: 99%